Clinical Effect on Early Rehabilitation Intervention of Patients after Coronary Artery bypass Grafting - Xin HE; Weiming ZHANG; Xin CHEN; Huijuan PAN; Yuanfeng SUN (康复学报)
Objective:To investigate the clinical effects of perioperative education and one-to-one rehabilitation training on patients undergoing coronary artery bypass grafting (CABG) surgery through exercise ability, pain, activities of daily living and mental status.Methods:A total of 204 patients in Ruijin Hospital of School of Medicine, Shanghai Jiaotong University, undergoing coronary artery bypass grafting were randomly divided into rehabilitation group and control group, with 102 cases in each group. Both groups were given routine post-operative care, and the patients in the rehabilitation group took part in an organized rehabilitation program and special instructional training related to diet and activities such as breathing, airway clearance, exercise and psychology education. The rehabilitation program started from the first 24 hours after surgery. The patients in the control group were given health education. The whole duration of the training last for 5 days in one week and twice in one day,30 minutes in every training. On the 7th day after the operation, quality of life assessment, pain,6-min walking test and mental status were performed to compare the health status, psychological status, and the relative walking distance were compared between the two groups.Results:On the 7th day after the operation,6-min walking test and the modified Barthel index (MBI) in the rehabilitation group were (354.75±85.83) metres and (92.79±5.34) scores respectively, which were significantly higher than the (295.60±67.83) metres and (83.82±6.22) scores in the control group (P<0.001). In addition, visual analogue scale (VAS) scores, Hamilton depression scale (HAMD) scores and Hamilton anxiety scale (HAMA) scores in the rehabilitation group were (1.19±0.55) scores, (10.46±8.21) scores and (11.36±4.87) scores respectively, which were significantly lower than those of the control group[ (1.88±1.29) scores, (17.22±6.15) scores, (19.58±6.72) scores, P<0.001].Conclusion:Early in-hospital cardiac rehabilitation intervention can effectively increase the 6-min walking distance, improve the patients'mental status and quality of life, and relieve pain.